Winner Picking in Urban Revitalization Policies: Empirical Evidence from Berlin - Felix Julius Richter (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This study addresses the question whether policy makers strategically pick winners when selecting the targets for place-based revitalization policies. It evaluates the influence of long-term trends of the unemployment rate and the share of residents of immigrant background on the probability of being selected as a target area, conditional on the current levels of these attributes. The empirical evidence is in line with the expectations: policy makers base their choice to some extent on the future performance expected of the areas. While high current levels of the unemployment rate increase the probability of being designated, increases in the unemployment rate over time decrease the probability of being selected. This effect is interpreted as winner picking: local authorities do not simply choose the most deprived areas, but instead prefer areas which show first signs of a gentrification process.
Keywords: R11; R23; R58; 330